Sigma Kappa Sorority (reverse) - Unknown (Tufts Archival Research Center, 2014)
This date is approximate. 8 x 6 in., photographic print. Back of photo showing members of the Sigma Kappa Sorority at Tufts posing on the steps of a building on campus.